Impact of Company Growth on Company Value in Property and Real Estate CompaniesRegisteredon the Indonesia Stock Exchange - Sumantyo, Franciscus Dwikotjo Sri (SEAN Institute, 2024)
The company's long-term goal is to optimize the value of the company by minimizing the company's cost of capital. The higher the value of the company, the more prosperous the owner of the company. The use of debt policy can be used to create the desired company value, but this policy also depends on the growth of the company which is also related to the size of the company. The purpose of this study is to analyze the company's growth on the firm value of property and real estate companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The research sample was 33 companies for 3 years so that there were 99 sample data. Data analysis used panel data regression analysis, using a data management program with the help of eviews version 9 software.